1997
DOI: 10.1063/1.365218
|View full text |Cite
|
Sign up to set email alerts
|

Electronic defect and trap-related current of (Ba0.4Sr0.6)TiO3 thin films

Abstract: By employing a deep level transient spectroscopy (DLTS) technique, this work investigates the deep trap levels of rf-sputtered (Ba0.4Sr0.6)TiO3 (BST) thin films deposited at various temperatures. Arrhenius plots of DLTS spectra detect a single trap located at 0.45 eV in 450 °C deposited films, whereas two traps located at 0.2 and 0.40 eV appear in 550 °C deposited films. On the other hand, examining the I–V characteristics of the films at the temperature range of 298–403 K reveals the presence of two conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…approximation method from which potential barrier height of 1.3 eV and trap ionization potential of 0.4 eV for the respective films were extracted. Interestingly, the numbers are found to be fairly comparable with the reported barrier height for the SE model, 35,36,43 and trap ionization energy for PF model 39,43 in BST and related perovskite thin films. The analysis in both films revealed that while the formation of Schottky potential barrier at the interface dominates the carrier transport in the undoped BST film, the BMN doped BST film is controlled by traps sitting in bulk of the film.…”
Section: Carrier Transport Mechanism In the Filmssupporting
confidence: 69%
“…approximation method from which potential barrier height of 1.3 eV and trap ionization potential of 0.4 eV for the respective films were extracted. Interestingly, the numbers are found to be fairly comparable with the reported barrier height for the SE model, 35,36,43 and trap ionization energy for PF model 39,43 in BST and related perovskite thin films. The analysis in both films revealed that while the formation of Schottky potential barrier at the interface dominates the carrier transport in the undoped BST film, the BMN doped BST film is controlled by traps sitting in bulk of the film.…”
Section: Carrier Transport Mechanism In the Filmssupporting
confidence: 69%
“…Fig. 4b shows that our data (data points) is consistent with the predictions for this mechanism (solid line), consistent with other reports that this mechanism dominates at high fields [22][23][24]. Fig.…”
Section: Resultssupporting
confidence: 94%
“…However, others have reported that that thermionic emission at internal interfaces, such as grain boundaries, can dominate conduction in Ba x Sr 1Àx-TiO 3 [22,23]. Although the observed thermally activated electrical properties (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Compared with previous results, it is reported the Schottky barrier height of SBT/SBN thin films in the range of about 1 eV [15,21]. The barrier height [24][25][26] of Ba 0.4 Sr 0.6 TiO 3 , Ta 2 O 5 and PZT thin films is 0.46 eV, 0.36 eV and about 0.6 eV, respectively. The Schottky barrier height of B = 0.2 eV for BLTV thin films is lower than that of other results.…”
Section: Resultsmentioning
confidence: 69%